EXPLORING OF THE PROTECTIVE EFFECTS OF CHINAR (PLATANUS ORIENTALIS L.) LEAF ON TESTES DAMAGE INDUCED BY ETHANOL IN RAT MODEL - Turan YAMAN; Abdulahad DOGAN; Ömer Faruk KELES; Fatih Dönmez; Abdulhamit BATTAL; Özgür Ozan Anuk (Journal of Animal and Plant Sciences, 2024)
The aim of this study was to investigate the protective effects of an infusion obtained from dried Chinar (Platanus orientalis L.; PO) leaves against ethanol-induced damage in rat testes. 30 male Wistar rats were divided into five groups: Control, Ethanol 20%, Ethanol 20% + Silymarin (10 mg/kg/day), Ethanol 20% + PO-20 mg/mL infusion and Ethanol 20% + PO-60 mg/mL infusion. Histopathologically, ethanol-induced damage, including the depletion of germ cells and loss of spermatozoa, was significantly improved in the Ethanol + PO-60 group. Immunohistochemically, an increase in the expression of endothelial nitric oxide synthase (eNOS) and caspase-3 was observed in ethanol group. Treatment with the PO extract markedly reduced the ethanol-induced expression of eNOS and caspase-3 in the Ethanol + PO-60 group. According to biochemical results, both of the PO infusion treatments caused decrease in malondialdehyde levels compare to ethanol group.  On the other hand, glutathione contents in treatment groups were significantly higher than ethanol group. Fluctuations in antioxidant defense enzyme levels were determined. PO leaf might have a protective role against ethanol-induced testicular damage in rats by inducing apoptosis via the upregulation of eNOS expression and preventing lipid peroxidation.
Keywords: Platanus orientalis; eNOS; caspase-3; Ethanol; Immunohistochemistery